The Influence of Turnover Factors Toward Employees’ Intention to Stay: A Case Study in Indonesian Islamic Universities - Nazaruddin Malik (Department Industrial Engineering, University of Muhammadiyah Malang, 2020)
This study analyzed employee turnover factors, such as satisfaction, organizational commitment, and religiosity, to predict the employees’ intention to stay. Very few studies in the Muslim context have explored such a corporate attitude from job satisfaction and organizational commitment. This study employed a quantitative and descriptive research design. A survey was used to analyze the correlation between some predictors of the employees’ intention to stay. In particular, it attempted to show that religiosity affected both job satisfaction and organizational commitment either directly or indirectly. The data were obtained from 150 employees in some Islamic universities in Malang, Indonesia. The findings revealed that religious beliefs influenced job satisfaction. Job satisfaction significantly affected the employees' commitment. Religiosity directly impacted corporate commitment through job satisfaction, and religiosity was positively related to the employees' intention to stay. Regarding this, the employees who keep religious beliefs in the workplace are encouraged to perform excellently.